2017
DOI: 10.1002/jcla.22309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of noninvasive and invasive point‐of‐care testing methods with reference method for hemoglobin measurement

Abstract: Predonation Hb measurements must be performed with accurate, precise, and practical methods. Although the noninvasive POCT method was practical and painless, it had lower levels of specificity and sensitivity, and more false deferral and pass rates than the invasive POCT method. The POCT methods agreeable to the venous method as the reference might be suitable for Hb screening especially for centers of excessive numbers of blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…One approach, as used in this study, involved drawing venous blood and laboratory measurement of full blood parameters. However, smaller devices that provide point-of-care metrics of haemoglobin and haematocrit are now available ( Nkrumah et al, 2011 ; Avcioglu et al, 2018 ; Singh et al, 2015 ). These devices require finger-prick samples of capillary blood, are quick, easy to obtain, and relatively non-invasive.…”
Section: Discussionmentioning
confidence: 99%
“…One approach, as used in this study, involved drawing venous blood and laboratory measurement of full blood parameters. However, smaller devices that provide point-of-care metrics of haemoglobin and haematocrit are now available ( Nkrumah et al, 2011 ; Avcioglu et al, 2018 ; Singh et al, 2015 ). These devices require finger-prick samples of capillary blood, are quick, easy to obtain, and relatively non-invasive.…”
Section: Discussionmentioning
confidence: 99%
“…The study design was a within‐person comparison, enhancing validity by providing head‐to‐head comparisons of different methods to measure haemoglobin concentrations. It involved evaluation of four methods, making it wider in scope than previous efforts focusing on fewer methods 7,9,32‐34 . It used a state‐of‐the‐art haematology analyser in an accredited central laboratory as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…One approach, as used in this study, involved drawing venous blood and laboratory measurement of full blood parameters. However, smaller devices that provide point-of-care metrics of haemoglobin and haematocrit are now available (Nkrumah et al, 2011;(Avcioglu et al, 2018;Singh et al, 2015). These devices require finger-prick samples of capillary blood, are quick, easy to obtain, and relatively non-invasive.…”
Section: Discussionmentioning
confidence: 99%
“…These devices require finger-prick samples of capillary blood, are quick, easy to obtain, and relatively non-invasive. Comparisons of point-of-care devices for measuring haemoglobin have been performed (Avcioglu et al, 2018;Singh et al, 2015). Avcioglu et al showed that the point-of-care measurement of haemoglobin was correlated with venous haemoglobin measures analysed with gold-standard cell analysers, with R 2 =0.825.…”
Section: Discussionmentioning
confidence: 99%